Evaluated bioactive component extracted from Punica granatum peel and its Ag NPs forms as mouthwash against dental plaque. (March 2019) - Esawy, Mona A.; Ragab, Tamer I.M.; Shalaby, Al Shimaa Gamal; Basha, Mona; Emam, Mahmoud
Abstract: The bioactive components of the hydroalcoholic (MeOH 70%) Punica granatum peel crude extract (PGPC) and its methanol fraction (PGPM) were extracted and tentatively identified by LCMS/MS as a number of phenolic compounds which are used as capping agents fasting the reduction of Ag + to Ag(0) . The prepared silver nano-particles Ag NPs PGPC and Ag NPs PGPM were characterized by the transmission electron microscopy (TEM) and UV–vis spectra. Four mouthwashes were designed using PGPC, PGPM, Ag NPs PGPC and Ag NPs PGPM. The prepared mouthwashes exhibited a significant antimicrobial activity against the Streptococcus mutans and the three dental plaque isolates called Lysinibacillus cresolivorans, Lysinibacillus cresolivorans and Lysinibacillus boronitolerans. As well as, the prepared Ag NPs mouthwashes led to reduction in the cytotoxicity against BJ-1 cell line equal 35 and 23.66% with LC50  = 185.16 and 134.8 μg/mL. Finally, phenolics promote Ag NPs PGPM mouthwash to be potent anti-calculus and anti-hemorrhagic agents.